How I maximised my training during the COVID-19 pandemic - H. Sekar; L. Berg; V. Sampson; W. Yoong (Journal of Obstetrics and Gynaecology)
The COVID-19 pandemic was declared in March 2020 and London maternity units were among the first in the United Kingdom to report maternal infection and vertical transmission. To manage resources, over half of all Obstetrics and Gynaecology trainees were redeployed to support front-line specialities such as Core Medicine and Accident and Emergency. The vignettes in this article illustrate how three trainees maximised their limited training opportunities in the face of exceptional disruption, lack of surgical training opportunities and workload pressures.